Ongoing impairments following transient ischaemic attack: retrospective cohort study. (19th July 2016) - Turner, G. M.; Calvert, M.; Feltham, M. G.; Ryan, R.; Marshall, T.
Abstract : Background and purpose: Clinical management after transient ischaemic attack (TIA) is focused on stroke prevention; however, a number of small studies suggest that patients may experience ongoing residual impairments. Methods: This was a retrospective matched‐cohort study using anonymized electronic primary care records from The Health Improvement Network database, which covers approximately 6% of the UK population. Adults (≥ 18 years old) who experienced a first TIA between 2009 and 2013 were matched in a ratio of 1:5 to controls by age, sex and general practice. The time to first consultation for fatigue, psychological impairment or cognitive impairment was estimated by Kaplan–Meier survivor functions and adjusted hazard ratios. Results: A total of 9419 TIA patients and 46 511 controls were included. The Kaplan–Meier curves showed that TIA patients were more likely than controls to consult for all three impairments ( P < 0.0001). Within 7.1 months (95% confidence interval (CI), 6.2–8.2), 25% of TIA patients consulted for psychological impairment compared with 23.5 months (95% CI, 22.5–24.6) for controls. Hazard ratios for TIA patients were 1.43 (95% CI, 1.33–1.54) for consulting for fatigue, 1.26 (95% CI, 1.20–1.31) for psychological impairment and 1.45 (95% CI, 1.28–1.65) for cognitive impairment. Conclusions: Transient ischaemic attack is associated with significantly increased subsequent consultation for fatigue, psychological impairment and cognitive impairment. These findings suggest that impairments exist after initial symptoms of TIA have resolved, which should be considered by clinicians when treating TIA patients. Abstract : Clickhere to view the accompanying paper in this issue.